The Affecting Factors of Maiz Farming Production in Rarampadende Village West Dolo District - Ellyani Ellyani; Made Antara; Lien Damayanti (Universitas Tadulako, 2016)
This study aims to determine the influence factors of land production, fertilizer, labor, seed and Dummy (seeds) as well as the agricultural extension to the production of maize in the village of Rarampadende, west Dolo District. The population in this study is the farmers who became members of farmers who run the farm corn amounted to 120 people, the number of samples is as many as 52 people, while the data were analyzed using multiple linear analysis of Cobb-Douglass. Results of the analysis showed that the production of the independent variables (Xi) together can have a significant effect on the dependent variable (Y). F-count value is equal to 27.103> F-table 2.44 (Significantly, 0,000 α 5%), in addition to the value of the coefficient of determination (R2 adjsSq) of 0.754 means that 75.40% of the variation in maize production (Y) can be explained by variable land area (X1), the number of seeds (X2) labor (X3), the amount of fertilizer (X4), seeds (D1) and agricultural extension (D2), while 24.6% can be explained other models. Land use, fertilizer, labor, seed, seeds and labor will simultaneously be able to affect the production of maize farming in Rarampadende village, West Dolo district.